2017
DOI: 10.3847/1538-4357/aa6892
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Quasi-periodic Oscillations and Time Lag in Ultraluminous X-Ray Sources with XMM-Newton

Abstract: We investigated the power density spectrum (PDS) and time lag of ultraluminous X-ray sources (ULXs) observed by XMM-Newton. We determined the PDSs for each ULX and found that five of them show intrinsic variability due to obvious quasi-periodic oscillations (QPOs) of mHz-1 Hz, consistent with previous reports. We further investigated these five ULXs to determine their possible time lag. The ULX QPOs exhibit a soft time lag that is linearly related to the QPO frequency. We discuss the likelihood of the ULX QPOs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…To date, the strongest claim of a soft-lag from a ULX is that for NGC 5408 X-1 (see Heil & Vaughan 2010, De Marco et al 2013, Hernandez-Garcia et al 2015 with QPOs observed between 10 and 38 mHz (De Marco et al 2013) with the soft band (0.3-1 keV) lagging the hard band (1-7 keV) by ≈ 1.5-5s at the QPO frequency (we note that soft lags have been reported in other ULXs at candidate QPO frequencies - Li et al 2017). Spectral fitting using a multi-colour disc blackbody component (in XSPEC this is through use of the DISKBB set of models which do not include a colour temperature correction: Mitsuda et al 1984) implies the temperature of the soft X-ray component in NGC 5408 X-1 lies between ≈ 0.12 -0.23 keV (see Soria et al 2004;Strohmayer & Mushotzky 2007;Middleton et al 2014;2015a).…”
Section: Ngc 5408 X-1supporting
confidence: 52%
“…To date, the strongest claim of a soft-lag from a ULX is that for NGC 5408 X-1 (see Heil & Vaughan 2010, De Marco et al 2013, Hernandez-Garcia et al 2015 with QPOs observed between 10 and 38 mHz (De Marco et al 2013) with the soft band (0.3-1 keV) lagging the hard band (1-7 keV) by ≈ 1.5-5s at the QPO frequency (we note that soft lags have been reported in other ULXs at candidate QPO frequencies - Li et al 2017). Spectral fitting using a multi-colour disc blackbody component (in XSPEC this is through use of the DISKBB set of models which do not include a colour temperature correction: Mitsuda et al 1984) implies the temperature of the soft X-ray component in NGC 5408 X-1 lies between ≈ 0.12 -0.23 keV (see Soria et al 2004;Strohmayer & Mushotzky 2007;Middleton et al 2014;2015a).…”
Section: Ngc 5408 X-1supporting
confidence: 52%
“…NGC 5408 X-1 shows the highest frequency soft lag that occurs at the same frequency as a broad quasi-periodic oscillation (QPO; Heil & Vaughan 2010;De Marco et al 2013;Li et al 2017). No such QPOs are found at the timescales of the soft lags in NGC 55 X-1 or here in NGC 1313 X-1, although in NGC 1313 X-1 the lag occurs over a broad frequency range, and so we cannot rule out that there is a broad Lorentzian in the power spectrum over this frequency range.…”
Section: Comparison To Other Ulxsmentioning
confidence: 99%